2022
DOI: 10.1029/2022gl098161
|View full text |Cite
|
Sign up to set email alerts
|

The Deuterium Isotopic Ratio of Water Released From the Martian Caps as Measured With TGO/NOMAD

Abstract: The evolution and history of water on Mars plays a key role in the assessment of the habitability of the planet across time. There is abundant geomorphological evidence suggesting that Mars had a wetter past (Bibring et al., 2006;Carr & Head, 2003), yet the duration and extent of this more humid past remains a topic of substantial debate. For instance, the large deltas, basins, and valleys on Mars are suggestive of large bodies of water that were stable over relatively long periods of time. Some estimates sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(60 citation statements)
references
References 58 publications
3
51
1
Order By: Relevance
“…As for the third source of the additional errors, the most dominant factor is the characterization of the AOTF transfer function. Villanueva et al (2022) showed that the light from nearby orders reaches detectors through the AOTF. By the solar calibration measurements, these signals from nearby orders are quantified for each diffraction order (Villanueva et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As for the third source of the additional errors, the most dominant factor is the characterization of the AOTF transfer function. Villanueva et al (2022) showed that the light from nearby orders reaches detectors through the AOTF. By the solar calibration measurements, these signals from nearby orders are quantified for each diffraction order (Villanueva et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Villanueva et al (2022) presents the up-to-date calibration of the NOMAD SO channel, which has been extensively improved from the earlier studies. The major updates presented in Villanueva et al (2022) are new characterization of (a) Instrumental line shape (ILS), and (b) AOTF transfer function. Villanueva et al (2022) showed that ILS is not an ideal Gaussian function but can be characterized by a sum of two Gaussian functions, whose parameters for each pixel are determined from the measurements of the Mars atmosphere.…”
Section: Instrument-nomad Onboard Tgomentioning
confidence: 99%
“…Recently, the calibration of the SO channel has been extensively updated (Villanueva et al., 2022). In this update, the AOTF transfer function has been reevaluated using inflight solar measurements, which allows us to significantly reduce the uncertainty and perform the molecular retrievals properly (Villanueva et al., 2022). The characterization of the instrumental line shape (ILS) has also been updated.…”
Section: Methodsmentioning
confidence: 99%
“…The characterization of the instrumental line shape (ILS) has also been updated. It was found that the ILS is not a simple Gaussian function but has an asymmetric shape (Thomas et al., 2021) that can be reproduced by a combination of two Gaussian functions (Villanueva et al., 2022). These latest updated instrumental functions were used in this analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation